2017
DOI: 10.1371/journal.pone.0178802
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of initial management of pneumothorax in adults: Intercostal tube drainage versus other invasive methods

Abstract: ObjectivesThe ideal invasive management as initial approach for pneumothorax (PTX) is still under debate. The purpose of this systematic review and meta-analysis was to examine the evidence for the effectiveness of intercostal tube drainage and other various invasive methods as the initial approach to all subtypes of PTX in adults.MethodsThree databases were searched from inception to May 29, 2016: MEDLINE, EMBASE, and the Cochrane CENTRAL. Randomised controlled trials that evaluated intercostal tube drainage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
(53 reference statements)
1
10
0
3
Order By: Relevance
“…Secondly, we performed strict inclusion and exclusion criteria. Kim et al's research (62), which published in 2017, didn't differentiate PSP and SSP without any subgroup analyses. While we researched on PSP but SSP, and included one recent study published in this year.…”
Section: Discussionmentioning
confidence: 98%
“…Secondly, we performed strict inclusion and exclusion criteria. Kim et al's research (62), which published in 2017, didn't differentiate PSP and SSP without any subgroup analyses. While we researched on PSP but SSP, and included one recent study published in this year.…”
Section: Discussionmentioning
confidence: 98%
“…The main goals in the management of PSP are to re-expand the lung and prevent recurrence, with minimal morbidity [19]. There are different therapeutic options described in literature for managing PSP: observation, air aspiration, placement of the chest tube, pleurodesis, thoracoscopy, and thoracotomy [20][21][22]. Chest tube drainage still remains the main option to manage the first episode of PSP.…”
Section: Discussionmentioning
confidence: 99%
“…There is a hypothesis that chest tube may irritate the pleural surface and may work like mechanical pleurodesis [14,30,31]. This probably could explain findings in some studies which showed that the recurrence rate after conservative management (without any intervention or only needle aspiration) is higher comparing to chest tube drainage [14,21,22,27].…”
Section: Discussionmentioning
confidence: 99%
“…Simple needle aspiration was associated with a reduction in the percentage of patients hospitalized when comparing it with intercostal tube insertion. Again, another recent meta-analysis by Kim and his colleagues [10] comparing seven studies for initial management of primary spontaneous pneumothorax showed that the recurrence rate of aspiration and intercostal tube drainage did not differ significantly, and again NA was associated with a shorter hospital patient stay. NA was however associated with inferior results regarding early resolution of pneumothorax in comparison to CTD.…”
Section: No Of Patientsmentioning
confidence: 99%